Rika Jansen poseert in struisvogeltenue uit haar one woman show 'Tussen plumes, pluche en plastic' - Meerendonk, Ben van,
Rika Jansen poseert in struisvogeltenue uit haar one woman show 'Tussen plumes, pluche en plastic'.